GENEALOGICAL TOURISM AND YOUTH DIPLOMACY: STRENGTHENING MUTUAL UNDERSTANDING THROUGH CULTURAL HERITAGE - Ismoilova Khumora Jamoliddin qizi (Modern American Journals, 2025)
This article explores the role and significance of genealogical tourism in youth diplomacy. Using the example of the Fergana Valley, it highlights the potential of genealogical heritage in strengthening international dialogue, diaspora relations, and intercultural understanding. The study is based on the historical-comparative method, the theory of collective memory, and tourism studies approaches. Special attention is given to the alignment of genealogical tourism with the UN Sustainable Development Goals. The findings demonstrate that genealogical tourism serves not only as a means of preserving cultural heritage but also as a strategic platform for youth diplomacy.
Keywords: Genealogical tourism; youth diplomacy; Fergana Valley; diaspora; family tree; cultural heritage.